INDUCED MUTAGENESIS IN CHRYSANTHEMUM MORIFOLIUM VARIETY ‘OTOME PINK’ THROUGH GAMMA IRRADIATION - KUMARI, KIRAN; K. K. DHATT; KAPOOR, MANISH (The Bioscan, 2013)
Rooted cuttings of chrysanthemum variety ‘Otome Pink’ were treated with 0, 10, 15 and 20 Gy of gamma rays and evaluated for various morphological, palynological and anatomical characters. Plant survival, plant height, number of flower heads, stems per plant, stem diameter and leaves per plant reduced after gamma irradiation. The delayed flowering and plant in vegetative stage were observed at 20 Gy gamma irradiation dose. Pollen fertility, number of chloroplasts per guard cell, flower head size and fresh weight also decreased as the dose increased. The leaf abnormalities were observed in terms of changes in leaf shape, leaf size, leaf margin and leaf apex. Flower head fasciation and asymmetrical development of flower heads increased with increased dose of gamma irradiation. Various changes in flower colour and shape were recorded after treatment in the form of chimeras. Two variants, one at 10 Gy having yellow colour and other at 15 Gy having quilled petals were obtained and further multiplied vegetatively.